Recovery of foot drop in chronic inflammatory demyelinating polyneuropathy (CIDP). Issue 1 (30th April 2021) - Weerasinghe, Dinushi; Veerapandiyan, Aravindhan; Stanton, Michael; Herrmann, David N.; Akmyradov, Chary; Logigian, Eric
Abstract: Introduction/Aims: Foot drop is common in chronic inflammatory demyelinating polyneuropathy (CIDP), but its prognosis is uncertain. Methods: CIDP patients with less than anti‐gravity strength (<3/5 power) of ankle dorsiflexion (ADF) on Medical Research Council manual muscle testing on presentation at our center were identified by retrospective review. After initiation of standard treatment, ADF power was serially tabulated, and predictors of recovery were determined. Results: Of the 27 identified patients, ADF power at presentation was <3/5 in 48/54 legs. At 1 y after treatment, ADF power improved to >/= 3/5 in 17/27 patients in one (N = 6) or both (N = 11) legs. On multi‐variate analysis, predictors of recovery of ADF power were tibialis anterior compound muscle action potential amplitude at presentation, shorter disease duration, and female gender. Discussion: Foot drop improves to anti‐gravity power in most treated CIDP patients depending in part on the severity of fibular motor axon loss at onset of treatment.